Genetic variation in LRP1 associates with Stanford Type B aortic dissection risk and clinical outcome - Erhart, Philipp; Körfer, Daniel; Grond-Ginsbach, Caspar; Qiao, Jia-Lu; Bischoff, Moritz; Hempel, Maja; Schaaf, Christian P.; Grau, Armin J.; Böckler, Dittmar (Journal of cardiovascular development and disease, 2022)
Genetic variation in LRP1 (low-density lipoprotein receptor-related protein 1) was reported to be associated with thoracic aortic dissections and aneurysms. The aims of this study were to confirm this association in a prospective single-center patient cohort of patients with acute Stanford type B aortic dissections (STBAD) and to assess the impact of LRP1 variation on clinical outcome. The single nucleotide variation (SNV) rs11172113 within the LRP1 gene was genotyped in 113 STBAD patients and 768 healthy control subjects from the same population. The T-allele of rs11172113 was more common in STBAD patients as compared to the reference group (72.6% vs. 59.6%) and confirmed to be an independent risk factor for STBAD (p = 0.002) after sex and age adjustment in a logistic regression model analyzing diabetes, smoking and hypertension as additional risk factors. Analysis of clinical follow-up (median follow-up 2.0 years) revealed that patients with the T-allele were more likely to suffer aorta-related complications (T-allele 75.6% vs. 63.8%; p = 0.022). In this study sample of STBAD patients, variation in LRP1 was an independent risk factor for STBAD and affected clinical outcome.
Gesehen am 08.06.2022